Revitalizing Religious-Based Mediation in Peripheral Indonesia: An Empirical Assessment of BP4's Role in Family Conflict Resolution - Amin, Nuzliyati; Abbas, Abd Haris; Abubakar, Fatum; Luthfi, Asma (ANTMIND YOUTH EMPOWER FOUNDATION, 2025)
This study investigates the effectiveness and institutional dynamics of religious-based mediation practices conducted by the Marriage Advisory, Development, and Preservation Agency (BP4) at the Religious Affairs Office (KUA) in South Morotai, Indonesia, a peripheral region marked by limited legal infrastructure and strong socio-cultural traditions. Using an empirical legal approach supported by interviews, observations, and document analysis, this research assesses BP4's mediation performance in resolving domestic conflicts, particularly between married couples, through the lenses of Soerjono Soekanto's legal effectiveness theory and the normative framework of Maqāṣid al-Sharī‘ah. Findings reveal that although BP4's formal structure has been inactive since 2018, its mediatory functions are still carried out informally by religious leaders and KUA officials. Mediation efforts, grounded in spiritual counseling and community-based norms, have helped reduce emotional tensions and divorce intentions in several cases. However, their effectiveness remains limited due to the absence of institutional protocols, trained mediators, standardized documentation, and post-mediation monitoring systems. This study contributes to the discourse on non-litigation dispute resolution in Muslim-majority societies by highlighting how informal religious authority can substitute and supplement state legal frameworks, particularly in under-resourced regions. It concludes that revitalizing BP4 as a functional mediation institution requires structural and regulatory reform and integrating psychosocial expertise, gender sensitivity, and the maqāṣid-oriented paradigm to ensure a more holistic, equitable, and sustainable family conflict resolution system.